RNA intermediates in potato spindle tuber viroid replication - Owens, Robert A. (1982)
Two double-stranded RNA intermediates of viroid replication have been isolated from potato spindle tuber viroid (PSTV)-infected tomato tissue and characterized by polyacrylamide gel electrophoresis and DNA-RNA hybridization techniques. These replicative intermediates contain monomeric circular or linear PSTV strands complexed with a multimeric complementary RNA strand. Synchronous synthesis of single-stranded PSTV is accompained by a simultaneous marked increase in double-stranded PSTV RNA; thus, in vivo precursors of the characterized double-stranded PSTV RNAs seem to be involved in PSTV replication. A “rolling circle” model for viroid replication on a circular PSTV template can accommodate the double-stranded PSTV RNA species characterized.